Design analysis and reconstruction of laboratory activities on fruit’s DNA isolation practice - Pangsuma, Nisa Sholehah; Supriatno, Bambang; Amprasto, Amprasto (Universitas Wiralodra, 2024)
Practicum is very important in science learning because it provides direct experience to students so that students can understand the context of natural phenomena through direct observation. This research aims to evaluate and improve the design of laboratory activities (DKL) in fruit DNA isolation practicum. This research uses a qualitative descriptive analysis design. The sampling method used was purposive sampling, namely by analyzing the DKL contained in Biology textbooks. The instrument used is an instrument development based on the Vee diagram principle. The results of the analysis show that DKL has a fairly good quality level, namely reaching a percentage of 72%, but still requires several adjustments in the form of reconstruction. The reconstruction carried out included adding verbs to learning objectives, replacing and adding equipment specifications, using standard units in measuring materials, restructuring procedures, adding units to observation tables, and data transformation using graphics. It is hoped that the results of the DKL reconstruction can provide more effective and relevant guidance for students and contribute to efforts to improve the quality of practical learning in the context of DNA isolation.